PERCEPTION OF VISUAL ART ELEMENT LINE ON FINE ART WORKS WITH PUPILS FROM I TO VI GRADE - Biljana Cvetkova Dimov (European Scientific Journal, ESJ, 2014)
In visual art education is existing segment that is neglected. This segment is aesthetic appreciation. Attendee of this paper is to represent the results of one part of influence and values of created model of work for aesthetic appreciation. The paper shows development of perception of visual art element line on fine art works with pupils from I to VI grade. Presenting the data obtained from the work of aesthetic appreciation we specifically single out the work on the development of perception. The obtained data confirm the previously established assumptions that between couple other phenomena studied and perception as a phenomenon can be developed through process of aesthetic appreciation.